The Connective Tissue Framework of the Hepatic Ligaments in the Human Liver - Khaltar, Purevsuren; Dalkhsuren, Shine-Od; Aldartsogt, Dolgorsuren; Sevjid, Badamjav; Sundui, Enebish (Central Asian Journal of Medical Sciences, 2020)
Objectives: To demonstrate the three-dimensional structure of the collagen fiber framework in the human liver ligaments and capsule. Methods: We studied the collagen fiber framework of relatively normal human liver specimens using a cell maceration method and scanning electron microscopy. Results: The collagen fibers of the hepatic falciform ligament subdivided into three types depending on the direction and location. The outer collagen fibers of the hepatic teres ligament formed the longitudinal plate, and the inner fibers had a loop-like structure. The coronary ligament contained two parallel collagen bundles toward the hepatic capsule. The hepatic capsule possesses the outer thicker and inner interlaced layers of the collagen fibers. The hepatic ligaments’ outer layer connected with the hepatic capsule collagen fibers, while the inner layer tended to merge with the hepatic lobular parenchyma’s connective tissue. Conclusions: The hepatic ligaments and liver capsule are layered structures of collagen fibers differing in direction. The hepatic ligaments’ outer layer connected with the liver capsule’s collagen fibers and the inner layer merged with the hepatic lobular parenchyma’s connective tissue.